Do Remittances Help Smooth Consumption During Health Shocks? Evidence From Jamaica - Diether W. Beuermann; Inder S. Ruprah; Ricardo E. Sierra (Inter-American Development Bank (IDB), 2014)
We identify whether remittances facilitate consumption smoothing during health shocks in Jamaica. In addition, we investigate whether remittances are subject to moral hazard by receivers, how the informal insurance provided by remittances interacts with formal health insurance, and whether there are differential effects by gender of the household head. We find that remittances offer complete insurance toward decreased consumption during health shocks and that moral hazard is weak. The role of remittances as a social insurance mechanism, however, is relevant only in the absence of private health insurance. No differential effects by gender of the household head are found.
hdl:11319/6537
Keywords: F24; I13; O15; 330; consumption smoothing; Jamaica; remittances; health shocks